2020
DOI: 10.1101/2020.10.26.353631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophilaclock cells use multiple mechanisms to transmit time-of-day signals in the brain

Abstract: Regulation of circadian behavior and physiology by the Drosophila brain clock requires communication from central clock neurons to downstream output regions, but the mechanism by which clock cells regulate downstream targets is not known. We show here that the pars intercerebralis (PI), previously identified as a target of the morning cells in the clock network, also receives input from evening cells. We determined that morning and evening clock neurons have time of day dependent connectivity to the PI, which … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
(87 reference statements)
1
7
0
Order By: Relevance
“…Indeed, the pace of DN1 molecular clock cycling is dictated by the speed of cycling in lateral clock cells ( Chatterjee et al., 2018 ; Stoleru et al., 2005 ; Yao et al., 2016 ; Zhang et al., 2010a ). Also consistent with an output function for DN1 cells is the fact that they are synaptically and functionally connected to multiple groups of non-clock output cells ( Barber et al., 2021 ; 2016 ; Cavanaugh et al., 2014 ; Guo et al., 2018 ; Jin et al., 2021 ; Lamaze et al., 2018 ; Tabuchi et al., 2018 ; Zhang et al., 2021a , 2021b ). Together, these results suggest a hierarchical organization, with DN1s lying downstream of the lateral clock neurons and serving as intermediaries that propagate pacemaker-derived circadian information to output regions that control behaviors.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Indeed, the pace of DN1 molecular clock cycling is dictated by the speed of cycling in lateral clock cells ( Chatterjee et al., 2018 ; Stoleru et al., 2005 ; Yao et al., 2016 ; Zhang et al., 2010a ). Also consistent with an output function for DN1 cells is the fact that they are synaptically and functionally connected to multiple groups of non-clock output cells ( Barber et al., 2021 ; 2016 ; Cavanaugh et al., 2014 ; Guo et al., 2018 ; Jin et al., 2021 ; Lamaze et al., 2018 ; Tabuchi et al., 2018 ; Zhang et al., 2021a , 2021b ). Together, these results suggest a hierarchical organization, with DN1s lying downstream of the lateral clock neurons and serving as intermediaries that propagate pacemaker-derived circadian information to output regions that control behaviors.…”
Section: Introductionsupporting
confidence: 57%
“…In support of this model, we also demonstrated that DN1p axons make close anatomical contact with PI output cells. Recently, this connectivity has been functionally confirmed through calcium imaging of PI cells during genetic activation of DN1p neurons ( Barber et al., 2021 ; Jin et al., 2021 ). However, given our current results that indicate that rest:activity rhythms persist in the face of Kir2.1 eGFP -mediated silencing of DN1p cells, it is clear that this DN1p to PI connection is not strictly necessary for circadian regulation of behavior.…”
Section: Discussionmentioning
confidence: 80%
“…While recent work has unraveled some clock output pathways to endocrine cells, our collective understanding of the circadian regulation of endocrine rhythms is poor (Nagy et al, 2019, King and Sehgal, 2020, Barber et al, 2021, Hidalgo et al, 2023. To address this knowledge gap, we first identified and classified all endocrine or NSC in the brain which are a major source of circulating hormones.…”
Section: Identification and Characterization Of The Neuroendocrine Ce...mentioning
confidence: 99%
“…Nonetheless, given the rich array of neuropeptides expressed in clock neurons, both synaptic and paracrine signaling appear crucial in mediating the connectivity between clock neurons as well as their output pathways. While recent work has begun to uncover some of this connectivity (Cavanaugh et al, 2014, Nagy et al, 2019, Barber et al, 2021, Reinhard et al, 2022a, Reinhard et al, 2022b, Shafer et al, 2022, Hidalgo et al, 2023, Kurogi et al, 2023, global analyses encompassing entire neuronal networks across both brain hemispheres are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation